Uncommon Infections in Children Suggest Underlying Immunodeficiency: A Case of Infective Endocarditis in a 3-Year-Old Male - Aisha Shakoor; Ahmed El-Isa; Elizabeth Kinsella; Ryan Halas; Andrey Leonov (Case Reports in Infectious Diseases)
Infective endocarditis (IE) results from bacterial or fungal infection and is associated with significant morbidity and mortality. Several known risk factors exist for endocarditis, and 90% of pediatric cases have an underlying structural or congenital heart disease or prosthetic heart valve. Literature on IE in previously healthy children is relatively sparse, and the pathogenesis and underlying risk factors remain mostly unknown. Our patient was a 3-year-old male with a unique presentation of IE. His lack of structural and congenital risk factors for endocarditis prompted further workup, and labs were consistent with insufficient immunoglobulin, suggesting a primary immunodeficiency (PAD). PAD presents as heightened susceptibility to infections, commonly seen as recurrent pneumonia, meningitis, septic arthritis, and otitis media. Pediatric patients commonly have infections, yet as many as in 1 in 2000 patients have PAD. Our case emphasizes the potential need for further investigation into PAD in a young patient with no known risk factors who develops an uncommon infection such as IE.